Population dynamics of blue crab (Paralithodes platypus Brandt, 1849) in the northwestern Bering Sea - P. A. Fedotov; I. S. Chernienko (Известия ТИНРО, 2022)
State of the blue crab stock and production is considered for the Russian sector of the Bering Sea on the data of bottom trawl and trap surveys conducted by TINRO in 2005–2017 and fishery statistics. The commercial stock was assessed for 2018 by cohort analysis. The absolute majority of commercial males within the West Bering Sea fishing zone concentrated in two areas located at Koryak coast and at Cape Navarin, whereas the commercial aggregations were absent in the Olyutorsky Bay and Karaginsky Bay. The stock distribution between these two areas was unstable; recently the aggregation at Koryak coast increased to 72 % of the total number of commercial males in 2017. This dynamics is conditioned by both changes in reproduction and intensity of fishery. The total commercial stock of blue crab had increased since 2014 and reached the maximum of 18.133 × 106 ind. (males) in 2017 that exceeded significantly the level of 2005–2013. The blue crab fishery extends in the Bering Sea, since 2010 the portion of used TAC increased from approximately 93 % in 2011–2015 to 98 % in 2016–2017 and 99 % in 2018. State of the population is evaluated as satisfactory and stable.